Mine ventilation : proceedings of the North American/Ninth US Mine Ventilation Symposium, Kingston/Ontario/Canada/8-12 June 2002 /: proceedings of the North American/Ninth US Mine Ventilation Symposium, Kingston/Ontario/Canada/8-12 June 2002. (2002) - Unknown
No abstract available